Sinais, sintomas e polimorfismos no gene COX2 associados a erupção dos dentes decíduos - Mauta, Alana Gonçalves (2019)
Tooth eruption is a long and complex biological process that includes the development and movement of teeth through the alveolar bone. Regarding the eruption of primary teeth, there is little scientific evidence to allow the association between signs and symptoms manifested by babies and perceived by family members. Despite the controversy over how parents perceive the signs and symptoms of tooth eruption, there is the same evidence that genetic polymorphisms in specific genes may contribute to the timing and sequence of tooth emergence in the oral cavity. The main objective of this study was to identify the signs and symptoms of tooth eruption presented by the child and to verify if there is an association between them and genetic polymorphisms in the COX2 gene. This is a cross-sectional study of 44 babies aged 9 to 48 months, of both sexes, recruited at the Positivo University's baby clinic, Curitiba, Brazil. The examination was performed by collecting epithelial cells from the oral cavity using a wooden spatula. These spatulas were then stored for later genetic testing. As a result, increased salivation (35; 79.5%), diarrhea (32; 72.3%), and febritis (31, 70.5%) were the most common reported and most noticeable signs and symptoms when incisors appeared. The average number of signs and symptoms of teething was observed in boys (p = 0.008). Regarding the genetic polymorphisms studied, it was not possible to prove the association between them and the signs and symptoms of tooth eruption.